Knowledge, Attitudes, Practices and Zoonotic Risk Perception of Bovine Q Fever (Coxiella burnetii) among Cattle Farmers and Veterinary Personnel in Northern Regions of Cameroon - Camille Teitsa Zangue; Justin Kouamo; Ferdinand Ngoula; Ludovic Pépin M’bapté Tawali; Moustapha Mohamed Fokom Ndebé; Dinayen Edwin Somnjom; Ranyl Noumedem Guefack Nguena; Mohamed Moctar Mouliom Mouiche (Epidemiologia, 2022)
A cross-sectional survey was conducted to investigate the knowledge, attitudes, practices and zoonotic risk perception of Q fever among 484 selected cattle farmers (438) and veterinary personnel (46) in three northern regions of Cameroon. Data collection was conducted using questionnaires and responses were recoded into binary scale. An ANOVA test was used to assess significant differences in mean knowledge, attitude, practice and zoonotic risk perception (KAPP) scores between regions, while Linear regression was done to explore the relationship between demographic characteristic and KAPP. Overall, surveyed had low mean scores for knowledge (0.02 ± 0.11), desirable attitude (0.30 ± 0.16), appropriate practice (0.43 ± 0.13) and negative perception of zoonotic risks (0.05 ± 0.11). The means knowledge, attitude, practice and risks perception scores of cattle farmers were lower than those of veterinary personnel. The nature of respondent was negatively associated to knowledge and risks perception, while regions were negatively correlated to attitude and practice. These results revealed significant knowledge gaps, low levels of desired attitudes, and high-risk behavioral practices. To improve awareness, control programs are needed to update knowledge on medical personnel and to prevent animal-to-human transmission.